(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Stunting is caused by low intake of nutrients in the long term and or frequent infections. Indonesia, which is a developing country, contributes to the growth of stunting in children under five in the world, where currently Indonesia is ranked fifth for stunting in children under five in the world. The aim of the study was to increase the knowledge and skills of mothers under five in the practice of improving health and preventing stunting in children under five in Pekik Nyaring Village, Central Bengkulu Regency. The pre-experimental design method, one group pre-test post-test, research subjects 30 mothers of children under five, were given training interventions using lecture methods, demonstrations and focus group discussions (FGD) and observation of mothers under five in 3 meetings. Data analysis with Wilcoxon test. The results of the study There were differences in the knowledge and skills of mothers of children under five before and after the training with a value (p-value